Technology Integration in Data Analysis using Data Science - Alwiyah (Pandawan Sejahtera Indonesia, 2023)
Nowadays, data has become a very important thing for an entity. Many entities are competing to utilize the information and data they have. Because of this, data analysis has become very important. However, with the increasing amount of data available, managing and analyzing data has become increasingly difficult with the methods used previously. With the development of technology, new data analysis methods can be used to overcome this problem. Nowadays, we have to cope with not only structured data but also unstructured data.